Epistemic Injustice: testimonial evidence and identity prejudice on crimes against women’s trials - Muniz Mardegan, Alexssandra (2023)
The patriarchal structures that still define Brazilian society are manifested in different forms of violence against women. The concept of epistemic injustice, developed by Miranda Fricker, is a key concept for understanding the impacts of identity prejudices in the trial of cases of violence against women, as it explains the distortions in the credibility distribution between aggressor and victim. Under this framework, endorsed by the bibliographical review of the specific literature, this article develops the hypothesis that the patriarchal power structures surface in epistemic practices, despite the presumed neutrality of the law, unbalancing the degree of credibility attributed to women and men in the context of criminal proceedings, and leading to injustices such as aggressors’ impunity and victim blaming based on gender stereotypes. Through this analysis, the article aims to answer: Fricker’s “virtuous hearer” ideal can be a helpful parameter to guide judicial hearings, especially regarding the judge’s posture towards victims of domestic abuse and other crimes against women? If so, how such virtuous epistemic practices can avoid negative gender biases on the evaluation of testimonial evidence, and ultimately contribute to diminish the harmful effects of identity prejudices in the justice system – given its inherent symbolic power?